Behavioural responses of a generalist predator to cues of plants harbouring various mixtures of prey - Silva, Laila Cristina Rezende (2019)
Foraging behaviour is fundamental in the lives of animals because finding food or hosts is essential for growth and reproduction. Many animals consume more than one type of resource mixed diets may increase their fitness. Consuming a mixed diet can redress nutritional imbalances of single resources and may dilute toxins present in food. However, resources often do not co-occur in time or space, hence, animals need to forage actively to obtain a mixed diet. To find food, animals use several cues, such as visual, vibrational, physical and chemical cues. Volatiles from prey and from plants under attack by the prey are important cues for many arthropods, including predatory mites. When attacked by more than one herbivore species, plants may release different volatiles compared to plants attacked by each herbivore separately. The generalist predatory mite Iphiseiodes zuluagai is associated with two main pests of Jatropha curcas: the broad mite Polyphagotarsonemus latus and the red spider mite Tetranychus bastosi. This predator feeds on both prey but has an increased performance when feeding on a mixture of both prey. Therefore, I investigated the foraging behaviour of I. zuluagai in a system composed of plants with both prey species or with either prey species separately. I found that this predator does not show a significant preference for plants with both prey, although it performs better on a diet consisting of both prey than on each prey alone. Furthermore, the predator does not show an innate olfactory preference. Thus, when this mite has no previous experience with these prey, it does not show a significant response to clean or attacked plants. Possible explanations for the apparent lack of preference of this mite are discussed, as well as the possible implications for biological control. Keywords: Mixed diet. Volatiles. Multiple infestation. Olfactometer.